Optimal Investment of DC Pension Plan under Incentive Schemes and Loss Aversion. (18th May 2020) - Dong, Yinghui; Lv, Wenxin; Wei, Siyuan; Gong, Yeyang
Abstract : We investigate the DC pension manager's portfolio problem when the manager is remunerated through two schemes for DC pension managerial compensation under loss aversion and minimum guarantee. We apply the concavification technique and a static Lagrangian technique to solve the problem and derive the closed-form representation of the optimal wealth and portfolio processes. Theoretical and numerical results show that the incentive schemes can significantly impact the distribution of the optimal terminal wealth.